Human Resource Management Competencies of Microenterprise Owners – A Review of Past Research in Poland - Olchawa, Fryderyk (Kompetencje właścicieli mikroprzedsiębiorstw z zakresu zarządzania zasobami ludzkimi – przegląd dotychczasowych badań w Polsce, 2025)
Aim: This study aimed to identify and discuss existing research in Poland on human resource management (HRM) competencies of microenterprises’ (ME) owners. The article categorises the knowledge of competencies and related terms, and identifies the main conclusions of past research on MEs and directions for future research. Methodology: This study was based on a systematic literature review of competency studies in MEs in Polish database. Results: The article summarises the research so far, including identifying its limitations and indicating future recommendations. The review highlights the lack of direct research on HRM competencies in MEs and their owners, thereby identifying the research gap and creating a contribution to further studies. Implications and recommendations: The article indicates the research gap for future research on MEs, and presents the collected recommendations for further research by the authors of the researched publications. Originality/value: The research contributes to the field of management and quality sciences, also supporting ME entrepreneurship, thus pointing to the country’s economic development as well as shed lighting on the existing research, identifying areas for future studies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 114-123